Gamification Design in Assisting Master's Students in Learning Readiness of XYZ University - Stanley Salim, Sebastian; Wang, Gunawan (International Journal of Engineering, Science and Information Technology, 2025)
This paper discusses how to design and assess a gamification framework to increase the learning preparedness of postgraduate students at XYZ University. Academic success at the master's level largely depends on learning readiness, and most students have to face numerous challenges, including poor time management, thesis composition, a lack of motivation, and insufficient social interaction with peers. Such obstacles inevitably result in low productivity and low engagement, which eventually influence the quality of their academic performance. In order to solve these problems, the concept of gamification is proposed as a new approach to pedagogy that incorporates the elements of a game into the learning process. The system included features like experience points (XP), leagues, leaderboards, and guided challenges to make the system more motivational, maintain engagement, and collaborate with students. The quantitative research design was chosen, and approximately 50 respondents who are enrolled in the program and participated in the gamified learning activities were used in the study. The results prove that gamification is a powerful tool that promotes learning preparedness by motivating success through reward systems and an opportunity to interact with peers through group activities and online discussion forums. The students claimed to be more motivated, better concentrated on the milestones of the thesis, and more disciplined in managing their time than they are using the traditional approaches. In addition, the system provides a more organised, interactive, and fun learning experience that allows participants to resolve academic difficulties more successfully. According to the assessment, the research indicates that gamification is an emerging tool that can be used to increase postgraduate learning preparedness. It suggests additional design improvements to the user interface, personalisation, and differentiation of reward systems to ensure the highest student engagement and effectiveness in the long term.